2020
DOI: 10.1136/jitc-2020-000584
|View full text |Cite
|
Sign up to set email alerts
|

Salvage ipilimumab associated with a significant response in sarcomatoid renal cell carcinoma

Abstract: BackgroundMetastatic sarcomatoid renal cell carcinoma (sRCC) is an aggressive variant of RCC with generally poor prognosis. Treatment with vascular endothelial growth factor inhibitors or chemotherapy generates only short-lived responses. Recent research has suggested a role for combination checkpoint inhibition as first line treatment for metastatic sRCC. This therapy consists of induction with cytotoxic T-lymphocyte-associated protein 4 inhibitor, ipilimumab, administered with programmed cell death protein 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Therefore, CTLA-4 blockade has profound effects on particular T-cell populations important in anti-tumor immunity [32]. George et al reported a case of sarcomatoid RCC that showed partial response to NIVO plus IPI and then progressed during maintenance therapy with NIVO [33], which is very similar to our case. The patient with sarcomatoid RCC was salvaged with the addition of IPI, which may suggest the importance of blocking CTLA-4 as well as PD-1 for sarcomatoid carcinoma.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, CTLA-4 blockade has profound effects on particular T-cell populations important in anti-tumor immunity [32]. George et al reported a case of sarcomatoid RCC that showed partial response to NIVO plus IPI and then progressed during maintenance therapy with NIVO [33], which is very similar to our case. The patient with sarcomatoid RCC was salvaged with the addition of IPI, which may suggest the importance of blocking CTLA-4 as well as PD-1 for sarcomatoid carcinoma.…”
Section: Discussionsupporting
confidence: 85%
“…In clinical practice, ICI combination therapy would be a better choice 19 , regardless of its complicating immune-related adverse events 20 . Moreover, since patients with mRCC and spindle histology received only a small benefit to survival in our study, ICI combination therapy seems a better strategy 21,22 . Specifically, combination therapy consisting of anti-CTLA-4 (ipilimumab) and anti-PD-1 (nivolumab) may be an optimal choice to treat this formidable disease 23 .…”
Section: Discussionmentioning
confidence: 74%
“…Durable control after cessation of ICI would allow for reintroduction of ICI at the point of progression or recurrence [ 40 ]. Rechallenge with combination anti-CTLA4 and anti-PD1 (e.g., Ipilimumab and Nivolumab) may also be a reasonable option in selected circumstances [ 41 ], which we had done with two patients in this series. The oncologist is challenged to maximize the clinical benefit of ICI therapy by his understanding of the atypical patterns of response.…”
Section: Discussionmentioning
confidence: 99%